The expression that represents the phrase is x - 6.4
The given parameters are:
Number = x
Value = 6.4
In mathematics, difference means subtraction, and it is represented by the "-" sign
So, the difference of a number x and 6.4 is: x - 6.4
Read more about algebraic expressions at:
The difference of two or more numbers simply means we subtract these numbers.
For example, the difference of 10 and 7 is 3.
Now, let's write the difference of x and 6.4 as an expression:
(Answer)
Hope you find it helpful.
Feel free to ask if you have any doubts.
THe closest answer i got was 18122
(1)f(x) = x² - 4x + 2, g(x) = 3x - 7
(f o g) (x) = f(g(x)) = f (3x - 7)
= (3x - 7)² - 4(3x - 7) + 2
= (9x² - 42x + 49) + (-12x + 28) + 2
= 9x² - 57x + 79
(2)g(x) = -6x + 5, h(x) = -9x - 11
(g o h) (x) = g(h(x)) = g (-9x - 11)
= -6(-9x - 11) + 5
= 54x + 66 + 5
= 54x + 71
(3)f(x) = √(2x - 5), g(x) = 5x² - 3
(g o f) (x) = g(f(x)) = g(√(2x - 5))
= 5 (√(2x - 5))² - 3
= 5 (2x - 5) - 3
= 10x - 25 - 3
= 10x - 28
Ο Α) π
B) 1.425
Oc) 50
OD) -4
Work out the annual rate of simple interest.
Answer:
2.4%
Step-by-step explanation:
Simple interest (I) is calculated as
I =
where P is the principal, R the rate of interest and T time in years
Here I = 96, P = 800 and T = 5, thus
96 = = = 40R ( divide both sides by 40 )
R = = 2.4%
(4x3+2x+1)÷(x+1)
4x2−4x+6+5x+1
4x2+4x−6−5x+1
4x2−4x+6−5x+1
4x2+4x+6−5x+1
4x2+4x−6−5x+1 is the solution for (4x3+2x+1)÷(x+1)
A division is a process of splitting a specific amount into equal parts.
We need to solve,
(4x3+2x+1)÷(x+1)
We use Synthetic division, Synthetic division is a shorthand method for dividing a polynomial by a linear factor such as x + 3, and it's much simpler and faster.
Step 1: Set up the synthetic division.
Step 2: Bring down the leading coefficient to the bottom row.
Step 3: Multiply by the value just written on the bottom row.
Step 4: Add the column created in step 3.
We get 4x2+4x−6−5x+1.
To learn more on Division click:
#SPJ2
Answer:
Step-by-step explanation:
(4x^3+2x+1)÷(x+1)
Using synthetic division is
4x^2-4x+6- 5/x+1